Self-imaging generation of plasmonic void arrays - Wang, Rong (EEE) (2013)
A plasmonic device is proposed to produce a self-imaging surface plasmon void array (2D surface bottle beam array) by the interference of two nondiffracting surface beams, namely, cosine-Gauss beams. The self-imaging surface voids are shown by full-wave calculations and then verified experimentally with an aperture-type near-field scanning optical microscope. We also demonstrate that the void array can be adjusted with flexibility in terms of the pattern and the number of voids